Estudo dos efeitos da obesidade associada à hiperglicemia sobre a perfusão miocárdica e a função ventricular em ratos wistar kyoto - SIQUEIRA, Ana Luísa Freitas (2021)
Introduction: Obesity is a chronic disease of multifactorial origin, characterized by the abnormal or excessive accumulation of fat in the adipose tissue as a result of the energy imbalance between consumption and the body's caloric expenditure. The implications of obesity are associated with the development and progression of several metabolic diseases, such as glucose intolerance, insulin resistance and diabetes mellitus, being one of the main risk factors for cardiovascular disease, capable of progressively injuring the vessel wall, triggering a process advanced inflammatory and impairing endothelial cell function. Alterations in left ventricular function, endothelial dysfunction and myocardial perfusion defects are frequently documented as a result of metabolic diseases. Thus, we suggest that experimental studies in animal models are important for understanding the pathophysiological mechanisms that influence the evolution of diseases such as obesity and those related to the sustained increase in blood glucose levels. Objectives: To evaluate myocardial perfusion, morphological and functional changes in the left ventricle and coronary flow reserve in an experimental model of young adult Wistar Kyoto rats induced to obesity and persistent hyperglycemia. Methods: 22-week-old Wistar Kyoto rats were used, kept in acclimatized accommodation in the vivarium of the Department of Clinical Medicine of the Faculty of Medicine of Ribeirão Preto - USP, allocated in a Control Group (CG, n = 10): Wistar Kyoto rats, aged 14 weeks of age, treated with standard chow, Hypercaloric Diet Group (DH, n = 12): Wistar Kyoto rats, 14 weeks of age, given a laboratory-prepared hypercaloric diet associated with fructose, and Hypercaloric Diet Group associated with Streptozotocin ( DH+STZ, n = 18): 14-week-old Wistar Kyoto rats that received the same food as the DH group, plus two injections of 30 mg/kg of STZ. After starting the experimentation protocol, the animals were submitted to weekly analysis of weight and blood glucose. After eight weeks of experimentation, all groups underwent the following in vivo imaging tests: Dopplertransthoracic echocardiography, coronary flow reserve, myocardial perfusion scintigraphy with Sestamibi-Tc-99m (SPECT) at rest and under pharmacological stress with dobutamine and glucose tolerance test. The induction of cardiac stress was performed by infusion ofdobutamine hydrochloride, at a dose of 25 µg/Kg/min, during one minute of infusion. The morphological parameters evaluated were left ventricular end-systolic and diastolic diameter, left ventricular posterior wall thickness in systole and diastole, interventricular septum thickness in systole and diastole, left ventricular mass index, relative ventricular wall thickness and peak coronary flow wave velocity under stress and at rest. The functional parameters evaluated were ejection fraction and left ventricular shortening. The uptake defects in resting and stress images were semiquantified by assigning visual scores (0 = normal; 1 = mild defect; 2 = moderate defect; and 3 = severe defect) in a 17-segment model of the left ventricular walls. For each animal, scores were calculated summed on images at rest, stress and difference between stress and rest to assess the global extent of reversibility (ischemia) and severity, measured through the difference score. At the end of the observation period, the animals were euthanized to remove blood serum. Results: The DH (336.6 ± 28.1 g, p < 0.0001) and DH+STZ (304.2 ± 19.2 g, p = 0.004) groups showed a significant increase in weight compared to the CG (330.1 ± 27.2 g); similarly in blood glucose, the DH+STZ group (123.7 ± 13.9 mg/dL) had higher values compared to the CG (83.0 ± 10.0 mg/dL, p < 0.0001) and to DH (105.3 ± 9.0 mg/dL, p < 0.03), as well as the DH group in relation to the control group (p < 0.005). In the glucose tolerance test it was observed that 15 minutes after glucose overload, blood glucose levels increased in all groups, being more expressive in DH (230.8 ± 54.9 mg/dL, p < 0.004) and DH +STZ (247.5 ± 44.5 mg/dL, p = 0.0006) when compared to the CG (166.3 ± 27.9 mg/dL); after 30 minutes blood glucose reached its peak, being still significant in the groups DH (250.9 ± 67.8 mg/dL, p = 0.0002) and DH+STZ (275.2 ± 58.5 mg/dL, p < 0.0001) compared to the CG (168.9 ± 25.6 mg/dL); after 60 minutes, the DH+STZ group (266.7 ± 59.7 mg/dL) still has high blood glucose when compared to the CG (132.3 ± 25.5 mg/dL, p < 0.0001) and DH (160.1 ± 28.1 mg/dL, p < 0.0001); 90 minutes later, DH+STZ blood glucose (205.3 ± 52.9 mg/dL) is still significantly higher when compared to CG (119.7 ± 19.5 mg/dL, p = 0.0003) and DH (135.5 ± 26.0 mg/dL, p < 0.003); after 120 minutes, blood glucose levels are similar between the three groups (p > 0.05). The morphological parameters observed in the ECO were similar between the experimental groups (p > 0.05). There was no significant difference in coronary flow values between the groups at rest, stress and coronary flow reserve (p > 0.05). There was also no significant difference in myocardial perfusion defects between the three groups (p > 0.05). Higher and significant values were documented for IL-6 in animals from the DH+STZ group compared to the CG (p < 0.04). Conclusions: A high-calorie diet associated with fructose in water and two low doses of streptozotocin induced obesity, promoted hyperglycemia, glucoseintolerance and mild inflammation, in an experimental obesity model in 22-week-old Wistar Kyoto rats. In the phase of evolution of metabolic disorders in which the animals were studied, the period of metabolic alteration was not sufficient to generate myocardial perfusion defects, ventricular remodeling and coronary microvascular dysfunction, suggesting further investigations for future projects, with a longitudinal design.